2005
DOI: 10.3354/meps298059
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the abundance and composition of picophytoplankton in relation to the occurrence of ‘Kyucho’ and bottom intrusion in Uchiumi Bay, Japan

Abstract: Uchiumi Bay experiences intermittent physical events of 'Kyucho ' and bottom intrusion.A Kyucho is an intrusion of warm surface water from the Kuroshio in the Pacific Ocean. Bottom intrusion, which contains a large amount of nitrates, phosphates, and silicates, slips through just above the continental shelf. We investigated seasonal changes in the abundance of Prochlorococcus, Synechococcus, and eukaryotic picophytoplankton while monitoring Kyucho and bottom intrusion from March to October 2002. Kyucho and bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 37 publications
(42 reference statements)
4
14
0
Order By: Relevance
“…Several studies of Japanese coastal waters have reported that the maximum abundance of cyanobacteria (PEC or Synechococcus spp.) is similarly within the range of about 1-3ϫ10 5 cells mL Ϫ1 (Odate 1989, Miyazono et al 1992, Shimada et al 1995, Koike et al 2001, Katano et al 2005; this agrees with our maximum values (1.1ϫ10 5 cells mL…”
supporting
confidence: 81%
“…Several studies of Japanese coastal waters have reported that the maximum abundance of cyanobacteria (PEC or Synechococcus spp.) is similarly within the range of about 1-3ϫ10 5 cells mL Ϫ1 (Odate 1989, Miyazono et al 1992, Shimada et al 1995, Koike et al 2001, Katano et al 2005; this agrees with our maximum values (1.1ϫ10 5 cells mL…”
supporting
confidence: 81%
“…Recently, we reported on the abundance of Prochlorococcus in a bay on the Bungo Channel (Katano et al 2005). We were also able to determine that Synechococcus in the bay consisted of a different type of PUB:PEB cells (Katano et al 2004, Katano & Nakano 2006.…”
Section: Introductionmentioning
confidence: 63%
“…In the East China Sea, no Prochlorococcus has been detected in coastal waters (Pan et al 2005). However, in Suruga Bay (Shimada et al 1995) and in Uchiumi Bay, located in the Bungo Channel (Katano et al 2005), Prochlorococcus has been detected. Since the Kyucho also occurs in Suruga Bay (Inaba et al 2003), the detected Prochlorococcus may have been transported from the open ocean.…”
Section: Advection Of Prokaryotic Picophytoplankton Resulting From Thmentioning
confidence: 98%
See 1 more Smart Citation
“…Since marine calanoid copepods often show species-specific feeding behavior and feed not only phytoplankton but also protozoan including ciliates that graze the microbial food web components, the feeding of calanoid copepods can affect the microorganisms through the food web cascade as well as phytoplankton community through direct grazing (Zöllner et al 2009). As eutrophication proceeds in estuaries and coastal areas, microbial food web components (e.g., bacteria, nanoflagellates, and ciliates) become key organisms in matter cycling (Katano et al 2005, Hirose et al 2008, and their interactions with herbivorous and omnivorous copepods have been considered as important linkage between microbial and herbivorous pathways in coastal marine ecosystems (Doi et al 2008, Chang et al 2009.…”
Section: Introductionmentioning
confidence: 99%